问题
解答题
计算与解方程: (1)33+(-32)+7-(-3) (2)-|-32|÷3×(-
(3)2(a2b-2ab2+c)-(2c+3a2b-ab2)、 (4)(-2)3-2×(-3)+|2-5|-(-1)2010 (5)化简求值:3x2y-[6xy-2(4xy-2)-x2y]+1,其中x=-
(6)已知多项式(2mx2+5x2+3x+1)-(5x2-4y2+3x)化简后不含x2项.求多项式2m3-[3m3-(4m-5)+m]的值. (7)解方程:①3x+3=2x+7 ②
|
答案
(1)原式=1+7+3=11;
(2)原式=-9×
×(-1 3
)+81 3
=1+8
=9;
(3)原式=2a2b-4ab2+2c-2c-3a2b+ab2,
=-a2b-3ab2.
(4)原式=-8+6+3-1=0;
(5)原式=3x2y-6xy+8xy-4+x2y+1=4x2y+2xy-3,
当x=-
时,原式=4x2y+2xy-3=-3.1 2
(6)(2mx2+5x2+3x+1)-(5x2-4y2+3x)化简得2mx2+4y2+1
∵化简后不含x2项.
∴2m=0即m=0,
∴2m3-[3m3-(4m-5)+m]=-5.
(7)①移项合并得:x=4;
②去分母得:4(x+1)=5(x+1)-6,
移项合并得:(x+1)=6,
∴可得:x=5.